Does international arbitration affect economic growth in Latin America? (2018)
In this paper, we examine the effects of international arbitration on GDP growth in Latin American countries. After reviewing the literature on the importance of arbitration from an economic standpoint, and by using a panel regression that allows us to control for country effects, we found that international arbitration has a positive effect on economic growth. Finally, to check for robustness, we control for country effects, and we find that the most relevant control variables that affect GDP growth are the current account deficit, inflation, income inequality, and the average duration of an arbitrage process in a specific country.